IMF Staff Papers, Volume 56, No. 2. (IMF Staff Papers; IMF Staff Papers, 2009)
China's growth performance since the start of economic reforms in 1978 has been impressive, but the gains have not been distributed equally across provinces. We use a nonparametric approach to analyze the variation in labor productivity growth across China's provinces. This approach imposes less structure on the data than the standard growth accounting framework and allows for a breakdown of labor productivity into efficiency gains, technological progress, and capital deepening. We have the following results. First, we find that on average capital deepening accounts for about 75 percent of total labor productivity growth, while efficiency and technological improvements account for about 7 and 18 percent, respectively. Second, technical change is not neutral. Third, whereas improvement in efficiency contributes to convergence in labor productivity between provinces, technical change contributes to productivity disparity across provinces. Finally, we find that foreign direct investment has a positive and significant effect on efficiency growth and technical progress.